Breakfast and subclinical atherosclerosis: a novel association that highlights the importance of dietary habits in the prevention of atherosclerotic diseases - Sanchez-Aranguren, Lissette; Ahmed, Asif (Annals of Research Hospitals, 2018)
Atherosclerosis is the prevailing cause of cardiovascular disease (CVD), including heart failure, ischemic stroke and peripheral vascular disease (1). It appears that behavioral risk factors, such as dietary patterns, are as important as physiological risk factors in the onset of CVD (2,3). Nonetheless, whether specific eating habits such as skipping breakfast regardless of nutrient composition can influence risk of CVD has started to be investigated.